Acceptor and Donor Dopants in Potassium Sodium Niobate Based Ceramics - Hussain, Fayaz; Khesro, Amir; Lu, Zhilun; Alotaibi, Nouf; Mohamad, Ahmad Azmin; Wang, Ge; Wang, Dawei; Zhou, Di (Frontiers in Materials, 2020)
B-site doping in potassium sodium niobate (KNN) with Mn2+ (M⁢nNb″′) and Ti4+ (T⁢iNb′) dopants were soluble but prevented KNN from achieving a high relative density, while Sn4+ (S⁢nNb′) was not soluble in the structure as evidenced by second phase peaks in X-ray diffraction (XRD) traces. However, SnO2 was an effective sintering aid in KNN-50/50. A-site doping with Sr2+ (S⁢r(Na,K)⋅) up to 1 mol% initially improved dielectric properties but higher sintering temperatures were required for compositions with >1 mol% Sr. Samples with 5% and 7% of Sr-doping completely shifted the transition of TO–T to below RT and broadened the TC peaks as the relaxor. All Ti-doped and Sr-doped compositions showed an increase in conductivity, manifested as high values of dielectric loss (tanδ). More than 1% of acceptor and donor dopants showed the ionic-type conduction mechanism, while 1% displayed the electronic mechanism as attributed from the strongly frequency-dependent tanδ. In conclusion, these samples have the potential to open up new applications in the field of electroceramics.